Prevalence and Clinical Profile of Peripheral Neuropathy among HIV Patients Visiting a Tertiary Care Hospital in North Karnataka: A Cross-Sectional Observational Study (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2025)
Introduction: Peripheral neuropathy (PN) is one of the most common neurological complications in people living withHIV (PLHIV). The increasing life expectancy of HIV-positive patients due to combination antiretroviral therapy (cART) has led to a growing burden of chronic neurological disorders, particularly HIV-associated peripheral neuropathy (HIV-PN). Despite its high prevalence, HIV-PN remains underdiagnosed, leading to significant morbidity and poor quality of life. The objectives  was to assess the prevalence of HIV-PN among HIV-positive individuals and to evaluate the demographic and clinical characteristics associated with HIV-PN.Methods: A cross-sectional observational study was conducted among 158 HIV-positive patients attending a tertiary care hospital in North Karnataka, India. Diagnosis of peripheral neuropathy was based on clinical symptoms, neurological examination, and nerve conduction studies (NCS). The Total Neuropathy Score (TNS) was used to grade peripheral neuropathy severity.Results: The prevalence of HIV-PN was 79.7%. The most common symptoms were tingling (85%), burning pain (76%), and numbness (62%), predominantly affecting the lower limbs in a length-dependent manner. Risk factors associated with peripheral neuropathy included longer HIV duration (p